\(x^2-3x=2\sqrt{x-1}-4\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{\sqrt{5}-\sqrt{3-\sqrt{29-12\sqrt{5}}}}\)
\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{20-2\sqrt{20.9}+9}}}\)
\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{\left(2\sqrt{5}-3\right)^2}}}\)
\(=\sqrt{\sqrt{5}-\sqrt{3-2\sqrt{5}+3}}\)
\(=\sqrt{\sqrt{5}-\sqrt{5-2\sqrt{5}+1}}\)
\(=\sqrt{\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}}\)
\(=\sqrt{\sqrt{5}-\sqrt{5}+1}\)
\(=\sqrt{1}=1\)
\(\frac{\sqrt{5}-\sqrt{15}}{1-\sqrt{3}}-\sqrt{21+4\sqrt{5}}\)
\(=\frac{\sqrt{5}\left(1-\sqrt{3}\right)}{1-\sqrt{3}}-\sqrt{5+2.2\sqrt{5}+4}\)
\(=\sqrt{5}-\sqrt{\left(\sqrt{5}+2\right)^2}\)
\(=\sqrt{5}-\sqrt{5}-2\)
\(=-2\)
\(\frac{1}{2\sqrt{n+1}}=\frac{1}{\sqrt{n+1}+\sqrt{n+1}}< \frac{1}{\sqrt{n+1}+\sqrt{n}}=\frac{\sqrt{n+1}-\sqrt{n}}{\left(\sqrt{n+1}-\sqrt{n}\right)\left(\sqrt{n+1}+\sqrt{n}\right)}=\frac{\sqrt{n+1}-\sqrt{n}}{n+1-n}=\sqrt{n+1}-\sqrt{n}\)
=> \(\frac{1}{2\sqrt{n+1}}< \sqrt{n+1}-\sqrt{n}\)(1)
\(\frac{1}{2\sqrt{n}}=\frac{1}{\sqrt{n}+\sqrt{n}}>\frac{1}{\sqrt{n+1}+\sqrt{n}}=\frac{\sqrt{n+1}-\sqrt{n}}{\left(\sqrt{n+1}-\sqrt{n}\right)\left(\sqrt{n+1}+\sqrt{n}\right)}=\frac{\sqrt{n+1}-\sqrt{n}}{n+1-n}=\sqrt{n+1}-\sqrt{n}\)=> \(\frac{1}{2\sqrt{n}}>\sqrt{n+1}-\sqrt{n}\)(2)
Từ (1) và (2) => \(\frac{1}{2\sqrt{n+1}}< \sqrt{n+1}-\sqrt{n}< \frac{1}{2\sqrt{n}}\)
\(\sqrt{14-8\sqrt{3}}\)\(=\sqrt{6-2.4.\sqrt{3}+8}\)
\(=\sqrt{\left(\sqrt{6}\right)^2-2\sqrt{3.16}+\left(\sqrt{8}\right)^2}\)
\(=\sqrt{\left(\sqrt{6}\right)^2-2\sqrt{48}+\left(\sqrt{8}\right)^2}\)
\(=\sqrt{\left(\sqrt{6}-\sqrt{8}\right)^2}\)
\(=\sqrt{6}-\sqrt{8}\)
1) \(x-y\)
\(=\left(\sqrt{x}\right)^2-\left(\sqrt{y}\right)^2\)
\(=\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)\)
2)\(1+x\sqrt{x}\)
\(=1^3+\left(\sqrt{x}\right)^3\)
\(=\left(1+\sqrt{x}\right)\left(1-\sqrt{x}+x\right)\)
\(x^2-3x=2\sqrt{x-1}-4\)
\(\Leftrightarrow\left(x^2-3x+4\right)^2=\left(2\sqrt{x-1}\right)^2\)
\(\Leftrightarrow x^4-6x^3+17x^2-24x+16=4x-4\)
\(\Leftrightarrow x^4-6x^3+17x^2-24x+16-4x+4=0\)
\(\Leftrightarrow x^4-6x^3+17x^2-2x+20=0\)
\(\Leftrightarrow\left(x^3-4x^2+9x-10\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left(x^2-2x+5\right)\left(x-2\right)=0\)
\(\Leftrightarrow x-2=0\)
\(\Leftrightarrow x=2\)
Vì: \(x^2-2x+5\ne0\)
\(\Rightarrow x=2\)
\(x^2-4x+4+x-1-2\sqrt{x-1}+1=0\)
=>\(\left(x-2\right)^2+\left(\sqrt{x-1}-1\right)^2=0\)
tự giải nốt